The Kremlin's candidate [compact disc, unabridged] : a novel - Matthews, Jason, 1951-2021- (Matthews, Jason, 1951-2021- Red Sparrow trilogy, 2018)
A junior American code clerk has defected to the Russians. He informs the Russian Foreign Intelligence Service that former US Secretary of Commerce Natalie Childers manipulated US global trade agreements to facilitate trade deals for the investment conglomerate owned by her husband. Natalie is now the Democratic presidential candidate, in the middle of a vigorous national campaign. Meanwhile double agent Dominika Egorova is ordered by Vladimir Putin to begin work on a special operation in which Russia will inform candidate Childers that her malfeasance will be made public unless she agrees to order Pentagon budget cuts, to propose debilitating reforms in NATO, and to move toward the dissolution of the Atlantic Alliance.